Digital Human Resource Management Practices and Employee Performance in MSMES: Evidence From Kupang City - Yunita Chrisna Riane Antonia Bere; Rena Saputri Hilaria Sitanggang; Maria Karmelita Delistiani Sambang (Indonesian Journal of Innovation Multidisipliner Research, 2026)
This study examines the influence of digital Human Resource Management (HRM) practices on employee performance in Micro, Small, and Medium Enterprises (MSMEs) in Kupang City, East Nusa Tenggara, Indonesia. Three dimensions of digital HRM were examined The Digital Technology Implemention in HRM (X1), Digital Training and Development (X2), and Digital Performance Management (X3) on Employee Performace (Y). Based on Resource-Based View (RBV) theory, this study employed a cross-sectional quantitative survey design with data collected from 39 MSME owners and managers through a structured online questionnaire (five-point Likert scale). Data were analysed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS procedures, including bootstrapping 5.000 subsamples for path coefficient significance. The measurement model demonstrated adequate reliability reliability and validity across all constructs (Composite Reliability: 0.905–0.940; Average Variance Extracted: 0.655–0.757). The structural model explains 75.7% of the variance in employee performance (R² = 0.757). Bootstrapping results confirm that Digital Technology Adoption has a significant positive effect on employee performance (β = 0.641, t = 5.274, p < 0.001, f² = 0.599 [large]), supporting H1. Digital Training and Development (β = −0.053, p = 0.645) and Digital Performance Management (β = 0.303, p = 0.083) did not reach the level of significance, thus failing to support H2 and H3. These findings highlight the importance of foundational digital tools as the a critical driver of employee performance in MSMEs in Eastern Indonesian with implications for practitioners and regional policymakers in NTT.